2004
DOI: 10.1108/09513540410543457
|View full text |Cite
|
Sign up to set email alerts
|

College tuition and perceptions of private university quality

Abstract: This research employs institutional characteristics and marketrelated factors to predict undergraduate students' tuition at 190 private colleges and universities in the USA. Results showed that the strongest correlations among variables for college tuition were reputation ranking and SAT scores. Results of a hierarchical multiple regression revealed that the type of institution, academic reputation ranking, the annual expenditures, geographic region, the existence of professional schools, the size of the facul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The private sector in higher education in the USA worked well for a number of economic, social and cultural reasons [23]. It had a history of 'decentralisation' and 'provincial autonomy' of governance and regulatory mechanisms throughout the country [24].…”
Section: Gatt and Gats Agreements And The Development Of The Private University Sectormentioning
confidence: 99%
“…The private sector in higher education in the USA worked well for a number of economic, social and cultural reasons [23]. It had a history of 'decentralisation' and 'provincial autonomy' of governance and regulatory mechanisms throughout the country [24].…”
Section: Gatt and Gats Agreements And The Development Of The Private University Sectormentioning
confidence: 99%
“…In the selection of English‐speaking colleges in Quebec, Canada, the reputation of the institution was one of the determinants (Isherwood, ). Teaching quality, staff qualifications, medium of instruction, reputation and institutional image related to academic staff are another set of determinants (Li‐Ping Tang, Shin‐Hsiung Tang, & Shin‐Yi Tang, ). The percentage of PhD qualified full‐time faculty at the institution is also considered important in the study by Baryla and Dotterweich ().…”
Section: Literature Reviewmentioning
confidence: 99%
“…With respect to brand positioning, the prior research (Gatfield et al, ; Gray et al, ; Mazzarol, ) has identified academic instruction and learning environment, campus life, reputation and career prospects for graduates as being the most salient dimensions in Higher Education. Not surprisingly, perceived quality (primarily as manifested by the courses offered) and reputation of an institution are among the strongest influences on student choice of institution (Chen & Hsiao, ; Mazzarol & Soutar, ; Wilkins & Huisman, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another aspect that also shows the trend of difference between PTN and PTS is the cost aspect. Li-Ping Tang (2004) stated that tuition fees at PTS are more expensive compared to PTN because the operational costs of institutions such as lecture facilities and infrastructure, lecturer salaries, and other operations are sourced from students. PTN tends to be cheaper in tuition fees because all operational costs are mostly financed by the state.…”
Section: Introductionmentioning
confidence: 99%